African Common Position for Sustainable, Resilient and Nature-positive Livestock Food Systems - Mbole-Kariuki, Dr. Mary; AU-IBAR (AU-IBAR, 2025)
The "Common African Position" is a coordinated approach developed by the African Union (AU) to represent Africa's collective interests and views on international matters on livestock. It is a platform for Africa to speak with one voice at global arenas in relation to advocating for livestock as a solution
Keywords: 37th General Conference of the International Scientific Council for Trypanosomiasis Research and Control (ISCTRC); Livestock food systems; Vector populations; Land degradations; Climate finance; Climate change governance